Proceedings of the 54th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2016
DOI: 10.18653/v1/p16-1029
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Domain Adaptation with Multiple Sources

Abstract: Domain adaptation is an important research topic in sentiment analysis area. Existing domain adaptation methods usually transfer sentiment knowledge from only one source domain to target domain. In this paper, we propose a new domain adaptation approach which can exploit sentiment knowledge from multiple source domains. We first extract both global and domain-specific sentiment knowledge from the data of multiple source domains using multi-task learning. Then we transfer them to target domain with the help of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 20 publications
0
72
0
Order By: Relevance
“…However, adaptation between two dissimilar domains is often undesirable, as it may lead to negative transfer (Rosenstein et al, 2005). Only recently, many-to-one adaptation (Mansour, 2009;Wu and Huang, 2016) has received some attention, as it replicates the realistic scenario of multiple source domains where performance on the target domain is the foremost objective.…”
Section: Background: Transfer Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…However, adaptation between two dissimilar domains is often undesirable, as it may lead to negative transfer (Rosenstein et al, 2005). Only recently, many-to-one adaptation (Mansour, 2009;Wu and Huang, 2016) has received some attention, as it replicates the realistic scenario of multiple source domains where performance on the target domain is the foremost objective.…”
Section: Background: Transfer Learningmentioning
confidence: 99%
“…As a reference, we also list the performance of the state-of-the-art multi-domain adaptation approach (Wu and Huang, 2016), which shows that task-independent data selection is in fact competitive with a task-specific, heuristic state-of-the-art domain adaptation approach. In fact our transferred similarity+diversity feature (E->D) outperforms the state-of-the-art (Wu and Huang, 2016) on DVD. This is encouraging as previous work (Remus, 2012) has shown that data selection and domain adaptation can be complementary.…”
Section: Transfer Across Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wu and Huang proposed new domain adaptation approach which maps sentiments from multiple source domains to target domain using sentiment graphs [21]. Sanju and Mirnalinee extracted unigram and bigram features from the reviews and selected best opinion features by computing relevance score and obtained 78% and 78.85% of accuracy using DVD and Books reviews respectively [22].…”
Section: Related Workmentioning
confidence: 99%